A Corpus-Based Analysis of the Meaning and Function of Although - Carbonell-Olivares, María (International Journal of English Studies, 2009)
The extent to which semantic and pragmatic descriptions of linguistic phenomena should be based on naturally occurring language is subject to debate. In the case of discourse markers and connective expressions, most research remains at a theoretical level, despite the increasing interest in the use of corpora for linguistic analysis in the last decades. We undertake a corpus-based analysis of the meaning and function of although, drawing on previous descriptions of this unit formulated from different theoretical perspectives (discourse analysis, pragmatics, semantics). We aim to contribute empirical evidence for certain claims made in the literature, and to complement such descriptions with our findings. The study focuses on the type of contrast expressed by although, the elements of the contrast relation and the structure of the information. First, the theoretical background for the particular issues we study is presented. Then, the objectives and methodology are explained, and results discussed.